Genetic variations suggests that Takifugu rubripes, T. chinensis, and T. pseudommus are the same species with a shared gene pool - Ji Young Lee; Kun Hee Kim; Hyuk Je Lee; Sun-Goo Hwang; Tae Sun Kang (Frontiers in Marine Science)
IntroductionPufferfish are valuable ingredients and important fishery resources in Asia. Among them, approximately 25 Takifugu species have undergone explosive speciation in the marine environments of East Asia. Specifically, T. rubripes, T. pseudommus, and T. chinensis are remarkably similar in appearance and genetics, and their classification remains controversial. Here, we provide comprehensive genetic and genomic evidence regarding their speciation and classification.MethodsWhole genome sequencing was performed on T. pseudommus, leading to the identification and development of 15 novel tandem simple sequence repeats (SSRs) from its genomic data. Genetic diversity, differentiation, and population structure among T. rubripes, T. pseudommus, T. chinensis, and T. xanthopterus were subsequently analyzed using a combination of these 15 SSR loci and mitochondrial cytochrome oxidase subunit I (CoI) and cytochrome b (CytB) gene sequences. Furthermore, genomic variations, including single nucleotide polymorphisms, insertions, and deletions, were identified by comparing the genome of T. pseudommus with the reference T. rubripes genome retrieved from the National Center for Biotechnology Information. These variations were screened using ENSEMBL annotation and gene ontology analysis, and their potential association with morphological differences, such as dorsal spot patterns, was evaluated using reference Takifugu specimens.Results and discussionPopulation genetic analysis of T. rubripes, T. pseudommus, and T. chinensis using the CoI and CytB genes, combined with the 15 SSR loci, revealed clustering into a single genetic group characterized by remarkably low genetic diversity (four haplotypes, with diversity values ranging from 0.0000 to 0.00065) and minimal pairwise differentiation (microsatellite-based FST values ranging from -0.0021 to 0.0075). Additionally, comparative genomic analysis between T. pseudommus and the reference T. rubripes genome did not identify genetic variations that could directly explain the observed morphological differences among the species. These findings strongly suggest that T. rubripes, T. pseudommus, and T. chinensis represent a single species sharing a common genetic pool.